Government interventions and equity liquidity in the sub-prime crisis period: Evidence from the ETF market - Chiu, Junmao; Tsai, Kunchi (My University, 2017)
Using bank bailout and funding injection actions to measure government interventions, this study explores whether the announcements of these actions could improve equity liquidity in the subprime crisis period. Our empirical results show that funding injections and bailout actions can both improve equity liquidity and increase net buying pressure, especially for the Paulson plan and the rescue of AIG from bankruptcy. The funding injection actions can improve equity liquidity more significantly than bailout actions.
Keywords: Bailout; Funding injection; Sub-prime crisis; Equity liquidity; Funding constraints